Pengembangan Atraksi Ekowisata Pesisir Melalui Identifikasi: Terumbu Karang, Lamun dan Mangroves (Studi Kasus: Ekosistem Wilayah Pesisir Dusun Rangko) - MARIUS YOSEF SERAN; Septian Hutagalung; Roseven Rudiyanto; Laurensius Sandrio; Fitri Ciptosari (JURNAL AKADEMISI VOKASI, 2023)
The coastal ecosystems identified are seagrass, mangroves forest, and coral reef ecosystems. Through this identification then this research aims to develop number of opportunities for developing coastal ecotourism through this observation and identification of mangroves, seagrass and coral reef ecosystems spread along several points in the coastal area of ​​Rangko’s Village. The method for data collection are qualitative description based on direct observation, field identification and documentation. The results shown that there is a diversity of coral reef, seagrass and mangrove ecosystems. Based on this finding can be concluded that the development of coastal ecotourism in Rangko’s coastal area has the opportunity to be developed through a number of ecotourism activities, such as snorkeling, fishing, paddleling, bird watching, and mangroves planting.